The role of sexuality symptoms in myeloproliferative neoplasm symptom burden and quality of life: An analysis by the MPN QOL International Study Group. Issue 12 (12th April 2016) - Geyer, Holly L.; Andreasson, Bjorn; Kosiorek, Heidi E.; Dueck, Amylou C.; Scherber, Robyn M.; Martin, Kari A.; Butler, Kristina A.; Harrison, Claire N.; Radia, Deepti H.; Cervantes, Francisco; Kiladjian, Jean‐Jacques; Reiter, Andreas; et al.
Abstract : BACKGROUND: Patients with myeloproliferative neoplasms (MPNs) including polycythemia vera, essential thrombocythemia, and myelofibrosis, are faced with oppressive symptom profiles that compromise daily functioning and quality of life. Among these symptoms, sexuality‐related symptoms have emerged as particularly prominent and largely unaddressed. In the current study, the authors evaluated how sexuality symptoms from MPN relate to other patient characteristics, disease features, treatments, and symptoms. METHODS: A total of 1971 patients with MPN (827 with essential thrombocythemia, 682 with polycythemia vera, 456 with myelofibrosis, and 6 classified as other) were prospectively evaluated and patient responses to the Myeloproliferative Neoplasm Symptom Assessment Form (MPN‐SAF) and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC‐QLQ C30) were collected, along with information regarding individual disease characteristics and laboratory data. Sexuality scores were compared with an age‐matched, healthy control population. RESULTS: Overall, patients with MPN were found to have greater sexual dysfunction compared with the healthy population (MPN‐SAF score of 3.6 vs 2.0; P <.001), with 64% of patients with MPN describing some degree of sexual dysfunction and 43% experiencing severe symptoms. The presence of sexual symptoms correlated closely with all domains of patient functionality (physical, social, cognitive, emotional, and role functioning) and were associated with a reduced quality of life. Sexual problems also were found to be associated with other MPN symptoms, particularly depression and nocturnal and microvascular‐related symptoms. Sexual dysfunction was more severe in patients aged >65 years and in those with cytopenias and transfusion requirements, and those receiving certain therapies such as immunomodulators or steroids. Conclusions: The results of the current study identify the topic of sexuality as a prominent issue for the MPN population, and this area would appear to benefit from additional investigation and management. Cancer 2016;122:1888–96. © 2016 American Cancer Society . Abstract : Sexuality problems impact all domains of functionality, depression, microvascular symptoms, and overall quality of life among patients with myeloproliferative neoplasms. These problems correlate with patient age, the presence of cytopenias, transfusion requirements, and common therapies for myeloproliferative neoplasms. See also pages 1804‐6.